DİVAN EDEBİYATINDA NAZIM ŞEKLİ MESELESİ - (:unkn) unknown (My University, 2017)
Nazım şekli terimi, divan edebiyatında bir manzumenin içeriği ve sanatsal özelliklerinin dışında kalan tarafını tarif eder. Dış yapıyla ilgili olan bu şekil kavramı, müşterek hususiyetler gösteren biçimler sayesinde kurallı ve sınıflandırılabilen bir bilgi sistemini karşılayan bir anlam kazanmıştır. Bundan dolayı edebiyat alanında yapılan çalışmalarda divan adlandırmalardan yola çıkılarak bütün şekiller tanımlanmaya ve kendi aralarında gruplandırılmaya çalışılmıştır. edebiyatının yazılı bulunduğu kaynaklarda yapılan adlandırmalardan yola çıkılarak bütün şekiller tanımlanmaya ve kendi aralarında gruplandırılmaya çalışılmıştır. Nazım şekillerini tarif eden ve sınıflandıran edebiyat çalışmalarında tam manasıyla birlik bulunmadığı gibi nazım şekillerini birbirlerinden ayırt edici vasıfları hakkında ve hangi ölçütlere dayanılarak gruplandırılacaklarına dair bir takım problemler bulunmaktadır. Bu meselenin ciddiyetini ortaya koyan Divan Edebiyatında Tür ve Şekil Bilgisi adlı çalışma, ortada olan sorunları masaya yatırmakla kalmayıp bunlara çözüm üretme arayışına girilen bir kitaptır. Dolayısıyla divan edebiyatında nazım şekillerinin hangi ölçütler altında tarif ve tasnif edileceği meselesini edenbiyat araştırmalarının gündemine getirmesi açısından dikkate değer bir çalışmadır. Bu makalede bahsi geçen çalışmanın işaret ettiği meseleler üzerinden gidilerek, edebiyat alanında nazım şekillerini anlatan kaynaklardaki bilgiler mukayeseli olarak incelenecektir. Mezkûr kitaptan önce yapılan çalışmalarda nazım şekillerinin nasıl anlaşıldığı, hangi kıstaslara göre tayin edildikleri ve neye istinaden tasnife tâbi tutuldukları irdelenecektir. Makalenin sonunda elde edilen sonuçlar Divan Edebiyatında Tür ve Şekil Bilgisi adlı kitaptaki yenilik ihtiva eden teklifler ile birlikte değerlendirilerek bütüncül bir neticeye ulaşılmaya çalışılacaktır.

The term of “nazım şekli” describes an exterior part of a poem, which means it does not include its contextual and rhetorical features in Ottoman literature. In this case the concept of “şekil” has acquired a meaning which is orderly and classifiable in the literary system due to the joined characteristics of poetic verse forms. Therefore, all the forms have been defined and classified in some of studies regarding Ottoman literature. The studies that describe and classify poetic verse forms do not show complete uniformness. Also they have some classification issues and distinguishing problems regarding the characteristics of each poetic verse forms. The book, Divan Edebiyatında Tür ve Şekil Bilgisi, did not only introduce the importance of the topic, but also attempted to solve the problems. On account of that, it is a noteworthy study because it has discussed and described the classifiying methods of poetic verse forms in Ottoman literature. This article will progress based on the aforementioned book. Other studies regarding the same topic will be examined in comparative way. Books that were written before Divan Edebiyatında Tür ve Şekil Bilgisi will be examined regarding how the poetic verse forms were understood and what kind of criterions were used. The results of the article will be assessed and new suggestions from the book will be given in order to yield a comprehensive conclusion The term of “nazım şekli” describes an exterior part of a poem, which means it does not include its contextual and rhetorical features in Ottoman literature. In this case the concept of “şekil” has acquired a meaning which is orderly and classifiable in the literary system due to the joined characteristics of poetic verse forms. Therefore, all the forms have been defined and classified in some of studies regarding Ottoman literature. The studies that describe and classify poetic verse forms do not show complete uniformness. Also they have some classification issues and distinguishing problems regarding the characteristics of each poetic verse forms. The book, Divan Edebiyatında Tür ve Şekil Bilgisi, did not only introduce the importance of the topic, but also attempted to solve the problems. On account of that, it is a noteworthy study because it has discussed and described the classifiying methods of poetic verse forms in Ottoman literature. This article will progress based on the aforementioned book. Other studies regarding the same topic will be examined in comparative way. Books that were written before Divan Edebiyatında Tür ve Şekil Bilgisi will be examined regarding how the poetic verse forms were understood and what kind of criterions were used. The results of the article will be assessed and new suggestions from the book will be given in order to yield a comprehensive conclusion.The classification of poetic verses is one major issue in the researches conducted in Ottoman Poetry. However, besides a book called Divan Edebiyatında Tür ve Şekil Bilgisi, none of the professional publications have approached the problem. It appears that the dissimilarity in classification is not considered a grotesqueness for researchers. The main reasons for the diversity in the classification of poetic verses is due to some variable criteria. The content, unit, length, meter and rhyme are the factors used to determine the poetic verse of the poem. However, regarding the classification of some specific poetic verses, all the factors were used at times and at other times only some of them were used. This circumstance causes a massive contradiction for an academical and scientific work. On account of the contradiction, firstly, one factor or more has to be appointed, then they can be used for the whole classifications. The book Divan Edebiyatında Tür ve Şekil Bilgisi argues that the rhyme is the only factor which determines the poetic verse in Ottoman poetry. The second criteria is the unit of the poetic verses, which consists of two styles; distich (beyt) and strophe (bend). The third factor is the “matla” which means opening distiches that rhyme together. Indeed rhyme is the most important thing in the distinction of poetic verses; however, it is never enough for precise distinction. For instance, there is no difference between rhyme of ode (gazel) and Idly (kaside). Also both are formed with distichs. As another example “rubai” and “tuyuğ” are both tetrastichs and have the same ryhme, but in order to distinguish the two poetic verses, there has to be another. According to other books regarding poetic verses in Ottoman poetry, meter is the only criteria to seperate rubai and tuyuğ. Divan Edebiyatında Tür ve Şekil Bilgisi argues that there should be a criteria that is to be used in all conditions. In other words, the same criteria provided should be used for all poetic verses; otherwise it cannot be accepted as a criteria. Since meter of the poetry is not mentioned to separate other poetic verses, this argument is fairly reasonable. Although criticisms of the book called Divan Edebiyatında Tür ve Şekil Bilgisi regarding other books that include poetic verses in Ottoman poetry are acceptable; suggestions of the book are not enough to solve problems because rhyme and unit are not enough criterias to seperate all the poetic verses. Because of that deficiency, the book Divan Edebiyatında Tür ve Şekil Bilgisi holds such marginal ideas; such as that Idly (kaside) is not a poetic verse but just a naming for a eulogy, whereas it has been used as a poetic verse for hundred of years in Ottoman poetry. When a poet decided to call his poem Idly (kaside) or ode (gazel) he did so without neglecting that there is no specific diversity between two poetic verses. As researchers, we can not ignore naming of the Ottoman poets themselves. The only way to the solution is to understand the reason why a poet called his poem as Idly (kaside), ode (gazel), enigma (muamma) etc. After that some immutable criterias that can be applicable for all poetic verses can be defined. In this article it is declared that as the book Divan Edebiyatında Tür ve Şekil Bilgisi suggested, rhyme and unit are the most important factors to determine poetic verses. At the same time, they are not enough to separate some poetic verses. If the content is accepted as another criteria, distinguishing between two poetic verses could be much easier, and as the book point out “matla” has to be one of the criteria to determine poetic verses. Accordingly, defining each poetic verse detachedly will be possible.
THE ISSUES OF POETIC VERSE IN OTTOMAN POETRY